Measurement of atmospheric neutrino mixing with improved IceCube DeepCore calibration and data processing - Abbasi, R.; Ackermann, M.; Adams, J.; Agarwalla, S. K.; Aguilar, J. A.; Ahlers, M.; Alameddine, J. M.; Amin, N. M.; Andeen, K.; Anton, Gisela; Argüelles, C.; Ashida, Y.; et al. (Physical Review D, 2023)
We describe a new data sample of IceCube DeepCore and report on the latest measurement of atmospheric neutrino oscillations obtained with data recorded between 2011-2019. The sample includes significant improvements in data calibration, detector simulation, and data processing, and the analysis benefits from a sophisticated treatment of systematic uncertainties, with significantly greater level of detail since our last study. By measuring the relative fluxes of neutrino flavors as a function of their reconstructed energies and arrival directions we constrain the atmospheric neutrino mixing parameters to be sin2θ23=0.51±0.05 and Δm322=2.41±0.07×10-3 eV2, assuming a normal mass ordering. The errors include both statistical and systematic uncertainties. The resulting 40% reduction in the error of both parameters with respect to our previous result makes this the most precise measurement of oscillation parameters using atmospheric neutrinos. Our results are also compatible and complementary to those obtained using neutrino beams from accelerators, which are obtained at lower neutrino energies and are subject to different sources of uncertainties.
CRIS-Team Scopus Importer:2023-08-25